2003
DOI: 10.1007/s00384-002-0423-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endoscopic ultrasonography in colorectal villous lesions

Abstract: It is difficult to determine the depth of invasion in villous lesions, especially large or rectal lesions, using only EUS. EUS-based evaluation alone cannot determine the appropriate treatment for colorectal villous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
2
6
1
1
Order By: Relevance
“…However, the accuracy of mEUS in differentiating between tumors of SM1 subclass or lower (M and SM1) and tumors of SM2 class or higher (SM2, SM3, muscularis propria, and serosa) was 85.7% (30/35). In the current study, we demonstrated that large tumor size decreased the accuracy of T staging by mEUS, which is consistent with the findings of other studies 4,25. Interestingly, in cases in which the tumor had invaded the submucosa and tumor size was >2 cm, the OR was 14.67 (95% CI, 1.46 to 146.96), suggesting that the accuracy of mEUS had dramatically decreased.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the accuracy of mEUS in differentiating between tumors of SM1 subclass or lower (M and SM1) and tumors of SM2 class or higher (SM2, SM3, muscularis propria, and serosa) was 85.7% (30/35). In the current study, we demonstrated that large tumor size decreased the accuracy of T staging by mEUS, which is consistent with the findings of other studies 4,25. Interestingly, in cases in which the tumor had invaded the submucosa and tumor size was >2 cm, the OR was 14.67 (95% CI, 1.46 to 146.96), suggesting that the accuracy of mEUS had dramatically decreased.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we suggest that extra caution should be taken when performing mEUS to predict the T stage in submucosal tumors that are >2 cm in size. Several studies have suggested that the accuracy of mEUS was lower in pedunculated-type tumors, villous lesions or tumors located in the rectum 13,25. However, in our study, the shape, location, and histopathological findings such as tumor differentiation or lymphovascular invasion had no effects on the accuracy of T staging by mEUS.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Pikarsky (56) from Cleveland Clinic showed that ERUS confirmed the histopathologic diagnosis of rectal villous tumor without evidence of malignancy in 26 out of 27 patients. Konishi et al (57) reported that the overall accuracy of ERUS-based evaluation of tumor invasion depth was 60% in villous lesions and 91% in non-villous lesions. In differentiating mucosa neoplasias (M)/ submucosal cancers with slight invasion (SM-s) from non M/SM-s the accuracy of ERUS in villous and nonvillous lesions was 66% and 96%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Une méta-analyse sur 11 études (1 791 patients) montre une sensibilité de 97,3 % (IC 95 % : 93,7-99,1) et une spécificité de 96,3 % (IC 95 % : 95,3-97,2) pour le diagnostic des lésions T0 [6]. L'écho-endoscopie surestime l'invasion de la sous-muqueuse pour différencier une invasion sm1 versus ≥ sm2 surtout pour les lésions villeuses rectales de grande taille (diamètre ≥ 20 mm ou hauteur ≥ 5 mm), avec une sensibilité de 60 %, une précision de 66 % mais une spécificité qui reste proche de 100 % [7].…”
Section: Diagnostic Endoscopique De Malignitéunclassified